Evaluation of group versus individual physiotherapy following lower limb intra-muscular Botulinum Toxin-Type A injections for ambulant children with cerebral palsy: A single-blind randomized comparison trial - Thomas, R.; Johnston, L.; Sakzewski, L.; Kentish, M.; Boyd, Roslyn (Pergamon Press, 2016)
© 2016 Elsevier Ltd. This study aimed to evaluate efficacy of group (GRP) versus individual (IND) physiotherapy rehabilitation following lower limb intramuscular injections of Botulinum Toxin-Type A (BoNT-A) for ambulant children with cerebral palsy (CP). Following lower limb BoNT-A injections, 34 children were randomly allocated to GRP (n = 17; mean age 7y8m SD 2.0; 13 males; Gross Motor Function Classification System (GMFCS) I = 5, II = 8, III = 4) or IND physiotherapy (n = 17; mean age 8y7m SD 2.0; 11 males; GMFCS I = 9, II = 5, III = 3). Primary outcomes were the Canadian Occupational Performance Measure (COPM) and Edinburgh Visual Gait Score (EVGS) assessed at baseline, 10 and 26 weeks post intervention. There were no baseline differences between groups. GRP intervention had greater, but not clinically meaningful, improvement in COPM satisfaction (estimated mean difference EMD 1.7, 95% CI 0.4-3.1; p < 0.01) at 26 weeks. Both groups demonstrated clinically significant improvements in COPM performance and satisfaction, but minimal change in quality of gait (EVGS). Six hours of direct physiotherapy (either GRP or IND) with an additional indirect dose (median 16 episodes) of individualized home programme activities following lower limb BoNT-A injections, however, was inadequate to drive clinically meaningful changes in lower limb motor outcomes.